Application Of Guided Inquiry-Based Worksheets In Utilizing Sugarcane Bagasse Waste As An Adsorbent Fe - Yunis Naini Hafsari Maulina; Yulia Sukmawardani; Saepudin Rahmatullah (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2024)
This study aims to describe the application of guided inquiry-based worksheets, describe students' scientific performance in learning, and analyze the effectiveness of using bagasse adsorbents in reducing Fe levels. The method used is a pre-experiment with the One Shoot Case Study design. The research subjects were students majoring in Chemistry Education at UIN Sunan Gunung Djati Bandung in the Separation Chemistry course with 15 students. The instruments used are worksheets and student scientific performance observation sheets. The ability of students to complete worksheets based on data obtained an average score of 92.5 in the very good category. While the scientific performance of students gets an average score of 89 in the very good category. Using sugarcane bagasse adsorbents in drilled wellwater samples also decreased Fe levels in samples taken from drilled well water at Al Ihsan Islamic boarding school by 34.2% and on campus II samples by 28.1%. This shows that the application of the worksheets on the use of bagasse waste as an Fe adsorbent can measure student scientific performance.